Comparison of three sequential extraction procedures for arsenic fractionation in highly polluted sites. (July 2017) - Wan, Xiang; Dong, Haochen; Feng, Liu; Lin, Zhijia; Luo, Qiuchen
Abstract: Three sequential extraction procedures (SEPs) including Tessier, Rauret, and Shiowatana SEPs, were compared for arsenic fractionation using highly polluted soils. In the definition context of exchangeable, reducible, oxidizable and residual fractions, with similar arsenic recovery and reproducibility, Tessier and Rauret SEPs were comparable to each other, whereas Shiowatana SEP showed higher extraction efficiency in all the first three arsenic fractions, although it might overestimate the reducible arsenic. Pot experiment indicated three SEPs all could provide an estimation of the most bioavailable arsenic fraction, and the application of Shiowatana SEP should be preferred. Accordingly, a case study with Shiowatana SEP for a site near a realgar mine area is conducted. The results show that although arsenic in this area presents predominantly in the stable fractions, the sum of most bioavailable fractions was accounted around 11% of total arsenic, and moreover, about another 10% of the total arsenic, the fourth fraction in Shiowatana SEP is likely to be transferred into bioavailable species under suitable conditions, such as strong acid impact, revealing a real major risk source being formed. The study indicated that Shiowatana should be more suitable for arsenic fractionation to provide valuable information in the framework of risk assessment. Highlights: With satisfied total recovery, Shiowatana SEP showed higher extraction efficiency in potentially mobile arsenic fractions. Shiowatana SEP was preferred and efficient for the most mobile arsenic extraction. Bioavailability evaluation on different arsenic fractions provides an insight to SEPs comparison. A case study applied by Shiowatana SEP shows potential risk in relevant areas.